Offering support to the general public by building CBT-based life skills: lessons learnt from an initial evaluation. (22nd February 2016) - Lyons, D.; Collins, K.; Hayes, C.
Abstract : Aims: Cognitive behavioural therapy (CBT) is effective for symptoms of mild to moderate depression yet access to such therapy is frequently limited. An alternative to traditional ways of delivering CBT is lower intensity methods based on self-help principles, using written CBT resources, in a group or class setting. Aware, the Irish National charity providing support to people experiencing depression, has implemented a 6-week CBT-based group programme which has been independently evaluated to demonstrate its effectiveness using quantitative and qualitative measures. Method: Two outcome measures (the Patient Health Questionnaire – PHQ-9, and Generalised Anxiety Disorder – GAD-7) were completed and analysed using a matched pairs t -test in respect of all participants at three intervals across the programme. Qualitative feedback was also sought upon completion of the course and offered insight into significant change and individual impact of the programme. Results: A total of 2289 individuals nationwide registered for the programme through the Aware website with 1885 completing the 6 weeks. There was an average attendance of 67% for the 6-week programme. Statistically significant reductions in terms of scores of depression and anxiety were seen upon completion but earlier trends towards improvement were noted. Conclusion: Completion of a 6-week Life Skills Programme has been associated with a reduction from moderately severe to mild scores in relation to both depressive and anxiety symptoms. Longitudinal follow-up will be required to determine if the effectiveness of the intervention is maintained but CBT-based group programmes may represent a useful alternative to traditional services to treat clinically significant depression.